Prolonged antiretroviral therapy is associated with fewer anal high-grade squamous intraepithelial lesions in HIV-positive MSM in a cross-sectional study. (30th March 2016) - Libois, Agnès; Feoli, Francesco; Nkuize, Marcel; Delforge, Marc; Konopnicki, Deborah; Clumeck, Nathan; De Wit, Stéphane
Abstract : Objective: HIV-positive men who have sex with men (MSM) are at increased risk of anal cancer. We evaluate the risk factors for anal high-grade squamous intraepithelial lesion (HSIL) (the precursor of anal cancer) in HIV-positive MSM. Methods: In this cross-sectional study within a cohort, 320 HIV-positive MSM were screened by anal cytology followed by high-resolution anoscopy (HRA) in case of abnormal cytology. Risk factors for anal HSIL were analysed. Results: Men were mostly middle-aged Caucasians with median CD4+ T lymphocytes of 638 cells/µL, 87% on combined antiretroviral therapy (cART) for a median of 5 years. 198 anal cytology samples were normal. In the 122 patients with abnormal cytology, HRA with biopsies were performed: 12% (n=15) normal, 36% (n=44) anal low-grade squamous intraepithelial lesion (LSIL) and 51% (n=63) anal HSIL. Comparing patients with or without anal HSIL (normal cytology or normal biopsy or LSIL), we found in multivariate analysis significantly fewer anal HSIL in patients with cART ≥24 months (OR 0.32 CI 95% 0.162 to 0.631, p=0.001). Conclusions: Prolonged cART (≥24 months) is associated with fewer anal HSIL.